Building the Treaty #3 Nibi Declaration Using an Anishinaabe Methodology of Ceremony, Language and Engagement - Aimée Craft; Lucas King (Water, 2021)
Ratified in 2019, the Nibi Declaration of Treaty #3 voices the relationship with water (Nibi) and jurisdictional responsibility that all Anishinaabe citizens have within the Treaty #3 territory. It affirms the responsibilities and relationships that others living within the territory should have with the water and ensures that the spirit of Nibi is central to decision-making and water governance. This article details the process of developing The Declaration, in accordance with the Treaty #3 lawmaking process and, which was driven by women, in ceremony, with the help of Gitiizii m-inaanik, and with the input of The Nation as a whole. This process embodies nationhood, sovereignty, and Anishinaabe jurisdiction as it relates to the environment and water, in accordance with the Manito Aki Inakonigaawin (Mother Earth law). Every person has a relationship with water. The process of nurturing that relationship through the teachings exemplified in the implementation of The Declaration will provide clarity on the responsibilities and partnerships that must be developed to protect the water for future generations.